Drama as Truth Commission: Reconciliation and Dealing with the Past in South African and Irish Theatre. Issue 1 (2nd January 2021) - Parr, Connal
Abstract : South Africa's Truth and Reconciliation Commission is an internationally regarded – if contested – touchstone for transitional justice, but it functioned above all as exemplary theatre, bringing together thousands of disparate voices. Like the theatrical space generally, it provided a forum for differing narratives about the past to be aired in post-Apartheid South Africa. In Ireland, on the other hand, there has not been – nor are we likely to see – any truth commission. It is this essay's contention that drama is the nearest the society will get to exploring the past, with the theatre a safe space in which storytelling and debates are taking place beyond the impasse of the political culture. This article approaches this through four plays: Athol Fugard's The Train Driver and Owen McCafferty's Quietly (both 2012) and David Ireland's Cyprus Avenue and Mongiwekhaya's I See You (both 2016). All reflect complications of dialogue(s) taking place on the past, and themes of reconciliation, in their respective territories.